Hybrid Dielectric Films of Inkjet‐Printable Core–Shell Nanoparticles. Issue 41 (23rd August 2021) - Buchheit, Roman; Kuttich, Björn; González‐García, Lola; Kraus, Tobias
Abstract : A new type of hybrid core–shell nanoparticle dielectric that is suitable for inkjet printing is introduced. Gold cores ( d core ≈ 4.5 nm diameter) are covalently grafted with thiol‐terminated polystyrene ( M n = 11000 Da and M n = 5000 Da) and used as inks to spin‐coat and inkjet‐print dielectric films. The dielectric layers have metal volume fractions of 5 to 21 vol% with either random or face‐centered‐cubic structures depending on the polymer length and grafting density. Films with 21 vol% metal have dielectric constants of 50@1 Hz. Structural and electrical characterization using transmission electron microscopy, small‐angle X‐ray scattering, and impedance spectroscopy indicates that classical random capacitor–resistor network models partially describe this hybrid material but fail at high metal fractions, where the covalently attached shell prevents percolation and ensures high dielectric constants without the risk of dielectric breakdown. A comparison of disordered to ordered films indicates that the network structure affects dielectric properties less than the metal content. The applicability of the new dielectric material is demonstrated by formulating inkjet inks and printing devices. An inkjet‐printed capacitor with an area of 0.79 mm 2 and a 17 nm thick dielectric had a capacitance of 2.2 ± 0.1 n F @ 1 k H z . Abstract : R. Buchheit, B. Kuttich, L. González‐García, T. Kraus A new type of core–shell nanoparticle dielectric that is suitable for inkjet printing is presented. Gold cores are covalently grafted with polystyrene. The resulting inks are used to spin‐coat and inkjet‐print dielectric films. The covalently attached shell prevents percolation and ensures high dielectric constants without the risk of dielectric breakdown.